(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Hypertension is extremely prevalent in patients with diabetes. Limited data exist on utilization patterns of antihypertensive in this population are consistent with evidence-based practice guidelines. Objective: The present study is aimed to evaluate utilization patterns of antihypertensive agents among hypertensive diabetic patients. Methodology: The study was conducted in the patient pharmacy department of Bangalore. A prospective observational study was conducted for a period of 6 months in at Tertiary Care Teaching Hospital, Bangalore, India. We included 150 hypertensive diabetic patients with or without other comorbid conditions and patients aged below 18 years and pregnant women were excluded. All the prescribed medications along with other medications and relevant information will be noted in a customized data collection. The study patients will be followed daily until their discharge. The Micromedex, Medscape, articles and relevant references books will be used as tools to review the collected data. The prescribed medication will be checked for their existence in the hospital and also the reelevating calculation. Check for any error in prescription such as doses, frequency and route of administration and analysis. Result: Out of 150 patients, 50% were male and 50% were female. Maximum patients belonged to age group of 51-60 years. Chronic Kidney Disease (18%) the was the most common associated disease with hypertension and diabetes mellitus. More than half of the patients had received one antihypertensive drug (60%), followed by two (28%), three (10%) and four (2%) antihypertensive drugs. Amlodipine (CCB) was the most commonly prescribed antihypertensive drug (64%). Conclusion: Amlodipine and furosemide were the most frequently prescribed antihypertensive drugs. Prescription of antihypertensive drugs for some patients with compelling indications were not in congruent with JNC 8 guidelines. This study highlights some therapeutic rationality in this health center. However, targeted education of the prescription-givers and dissemination of treatment guideline could facilitate rational use of drugs and adherence to treatment guide lines.